2013
DOI: 10.1136/bcr-2012-007575
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster as a cause of viral meningitis in immunocompetent patients

Abstract: A 30-year-old Caucasian woman, without significant medical history or immunosuppression, presented with a 7-day history of severe headache and neck pain. The patient was presumed to have tension headache versus migraine, but was admitted because her symptoms did not resolve. A lumbar puncture was performed showing lymphocytic pleocytosis suggestive of aseptic meningitis and the patient was started on broad-spectrum antibiotics and acyclovir. After admission, a rash was discovered on her left lumbar region with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
2
16
0
1
Order By: Relevance
“…Aseptic meningitis prior to vesicular eruption was notable presentation in our patient as Takeshima et al reported only two of 11 cases had herpes zoster meningitis prior to the dermatological lesion [4]. Similar to our case, herpes zoster aseptic meningitis preceding dermatological rash was reported by Kangath et al [5].…”
Section: Case Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Aseptic meningitis prior to vesicular eruption was notable presentation in our patient as Takeshima et al reported only two of 11 cases had herpes zoster meningitis prior to the dermatological lesion [4]. Similar to our case, herpes zoster aseptic meningitis preceding dermatological rash was reported by Kangath et al [5].…”
Section: Case Discussionsupporting
confidence: 87%
“…However, our patient was a young adult with herpes zoster infection presenting as aseptic meningitis and dermatomal rash that make his presentation unique. A similar case report of herpes zoster in the young adult was reported by Kangath et al [5]. Most of the patients with herpes zoster commonly occurred in the immunocompromised people as reviewed by the Bollea-Garlatti et al [6]; however, our patient had negative workup for immunocompromised status.…”
Section: Case Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It is underdiagnosed due to the lack of availability of PCR and intrathecal testing of varicella zoster virus compared with herpes simplex virus (HSV) testing which is readily available in healthcare facilities. 4 Because of its low incidence, atypical presentation and unavailability of testing, diagnosis requires high index of suspicion. Isolated neurological symptoms presenting without dermatomal rash can be easily be missed once HSV meningitis is ruled out and can result in premature cessation of antivirals.…”
Section: Discussionmentioning
confidence: 99%
“…Cases have been reported where meningitis has present solely with rash without preherpetic or postherpetic neuralgia as occurred in our case. 4 If dermatomal pain is the only finding, it is known as zoster sine herpete (ZSH).…”
Section: Discussionmentioning
confidence: 99%